The Parliament of Man : The Past, Present, and Future of the United Nations - Kennedy, Paul M., 1945- (New York Random House, 2006)
Scholar Kennedy gives a thorough history of the United Nations that explains the institution's roots and functions while also casting an eye on the UN's effectiveness as a body and on its prospects for success in meeting coming challenges. He makes sense of the commissions and committees, and how the six main operating bodies operate and interact
Include Notes, Index, and Appendix
Keywords: United Nations -- History -- International Relations -- Nations Unies - Histoire